2018
DOI: 10.1097/md.0000000000013363
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is poor prognostic factor in older patients with locally advanced rectal cancer who received preoperative or postoperative chemoradiotherapy

Abstract: Sarcopenia is associated with low muscle mass and low physical performance. Here, we performed to evaluate the sarcopenia as prognostic factor and treatment outcomes in older patients with locally advanced rectal cancer (LARC) who received preoperative or postoperative chemoradiotherapy (CRT).LARC patients aged ≥65 years who received either preoperative or postoperative CRT were analyzed retrospectively. Preoperative or postoperative CRT consisted of 50.4 Gy and fluoropyrimidine. Surgery was performed at 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 22 publications
(27 reference statements)
3
43
0
1
Order By: Relevance
“…Additionally, in a study of 70 older patients (median age: 71 years) who received neoadjuvant or adjuvant chemoradiation for rectal cancer, low skeletal muscle index (muscle depletion) was associated with a higher hazard ratio (HR) for death (6.01; p = 0.001). This HR was higher than that for age, sex, cancer stage and carcinoembryonic antigen (CEA) level [62].…”
Section: Outcomes In Older Adults With Cancer and Wasting Disordersmentioning
confidence: 73%
“…Additionally, in a study of 70 older patients (median age: 71 years) who received neoadjuvant or adjuvant chemoradiation for rectal cancer, low skeletal muscle index (muscle depletion) was associated with a higher hazard ratio (HR) for death (6.01; p = 0.001). This HR was higher than that for age, sex, cancer stage and carcinoembryonic antigen (CEA) level [62].…”
Section: Outcomes In Older Adults With Cancer and Wasting Disordersmentioning
confidence: 73%
“…The current body of evidence shows inconsistent associations between body composition measures and adverse outcomes in patients with CRC. Low SM has been shown to be associated with severe postoperative complications , LOS , dose‐limiting toxicity , and long‐term survival . However, other studies did not show associations between low SM and overall or severe postoperative complications , readmission , and long‐term survival .…”
Section: Discussionmentioning
confidence: 97%
“…These varying results may have been caused by the use of different cutoff points, limiting comparison of studies. Another explanation for the inconsistency in the literature could be the inclusion of all age groups, as only one study specifically included older patients and found a significant association between low muscle mass and overall survival in patients with rectal cancer receiving chemoradiation . The association between CT‐based body composition measures and adverse outcomes is expected to differ between younger and older populations as body composition measures are negatively affected by age but still show inconsistency when only studies with a mean/median age of 65 years and older are considered.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle index (SMI) was calculated as total L3 skeletal muscle divided by height squared. Sex‐specific thresholds of sarcopenia were 52.4 cm 2 /m 2 for men and 38.5 cm 2 /m 2 for women 11,12 …”
Section: Methodsmentioning
confidence: 99%